The Desire to Rethink Power AND Performativity AND Process. Issue 12 (December 2021) - Fouweather, Ian; Bosma, Bas
Power AND performativity AND process. Three concepts. Three theoretical perspectives that shape current studies of organizing, of organizations, how they come into existence and how they are maintained. Three distinct trajectories that have already been traced; their separate articulations creating tension, paradox and contradiction. Can we resist existing conceptualizations to create new immanent relations? Can we dissolve the necessity of binary logics, of order, of finality, and embrace simultaneity and multiplicity? In this paper we reimagine the interplay between power and performativity, embracing the role of resistance within the emergent micro-processes of organizational becoming. To do this we take inspiration from the work of Gilles Deleuze.